Deoxynivalenol Impairs Porcine Intestinal Host Defense Peptide Expression in Weaned Piglets and IPEC-J2 Cells - Wang, Shuai (Toxins (Basel), 2018)
Host defense peptides (HDPs) are efficient defense components of the innate immune system, playing critical roles in intestinal homeostasis and protection against pathogens. This study aims to investigate the interference effects of DON on the intestinal porcine HDPs expression in piglets and intestinal porcine epithelial cell line (IPEC-J2) cells, and elucidate the underlying mechanisms through which it functions. In an animal experiment, intestinal HDPs were determined in weaned piglets fed control and 1.28 mg/kg or 2.89 mg/kg DON-contaminated diets. Dietary exposure to DON significantly decreased piglet average daily gain, increased intestinal permeability and depressed the expression of porcine β-defensin1 (pBD1), pBD2, pBD3, epididymis protein 2 splicing variant C (pEP2C), PMAP23, and proline/arginine-rich peptide of 39 amino acids (PR39) in the intestine (p < 0.05). In IPEC-J2 cells, DON decreased cell viability and inhibited the expression of pBD1, pBD3, pEP2C, PG1-5, and PR39 (p < 0.05). NOD2, key regulator that is responsible for HDPs production, was markedly downregulated, whereas caspase-12 was activated in the presence of DON. In conclusion, DON induced caspase-12 activation and inhibited the NOD2-mediated HDPs production, which led to an impaired intestinal barrier integrity of weaned piglets. Our study provides a promising target for future therapeutic strategies to prevent the adverse effects of DON.